“I must be perfect”: The role of irrational beliefs and perfectionism on the competitive anxiety of Hungarian athletes - Tóth, Renátó; Turner, Martin J.; Kökény, Tibor; Tóth, László (Frontiers in Psychology, 2022)
In this study the influence of irrational beliefs and perfectionism on the emergence of competitive anxiety was investigated. While previous studies indicate that higher irrational beliefs predict greater competitive anxiety, in the present study it is hypothesized that this relationship is mediated by perfectionism. A serial atemporal multiple mediation analysis revealed that both adaptive and maladaptive perfectionism were significant partial mediators between irrational beliefs and competitive anxiety. The total score and all four subscale scores on irrational beliefs had both direct and indirect effects on cognitive competitive anxiety, the latter effects mediated by both forms of perfectionism. Depreciation beliefs had a direct effect, and demandingness and awfulizing had indirect effects, on somatic competitive anxiety when both forms of perfectionism were entered as mediators. These findings suggest that both irrational beliefs and perfectionism influence the emergence of competitive anxiety, therefore rational emotive behavioral therapy with a focus upon perfectionism may be an effective means of reducing competitive anxiety in athletes.